Experimental Evaluation of the Punching Shear Strength of Interior Slab-column Connections with Different Shear Reinforcement Details - Rasha Mabrouk; Gehad Younis; Osman Ramadan (Civil Engineering Journal, 2022)
This research aims to evaluate the effect of using different shear reinforcement details on the punching shear behavior of interior slab column connections. A comprehensive experimental program is conducted on sixteen specimens having the same concrete dimensions of 1100×1100×160 mm where the slab depth is chosen to be less than that stipulated by different design codes. The parameters under examination were the type of shear reinforcement arranged in a cross shape perpendicular to the column edges (single leg, multi-leg, and closed stirrups), the spacing between stirrups (25 and 50 mm), and the extended length covered by the stirrups (300 and 425 mm). Experimental results showed that slabs reinforced with multi-leg or closed stirrups, even for slabs with a thickness of 160 mm, had an increase in the shear capacity by up to 40% depending on the stirrup amount. A noticeable enhancement in ductility was also observed. Slabs reinforced with vertical single-leg stirrups did not exhibit any improvements. A finite element analysis was conducted to further assess the punching shear behavior of the tested specimens. A comparison between the test results and values obtained using design codes such as ACI 318-19 and ECP 203-2018 showed that the two design codes give a rather underestimated prediction of the punching shear capacity. Doi: 10.28991/CEJ-2022-08-09-015 Full Text: PDF